2022
DOI: 10.1002/cre2.539
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological role of vitamin D deficiency in recurrent/chronic tonsillitis pathogenesis: Vascular epithelial growth factor‐mediated angiogenesis in tonsil

Abstract: Objectives: Our aim in this study is to reveal the role of vitamin D deficiency in the pathogenesis of recurrent/chronic tonsillitis and to determine the expression of vascular epithelial growth factor (VEGF).Material and Methods: This study was conducted between September and February.Thirty-two patients between the ages of 3 and 35 (mean age 9.71) with recurrent episodes of chronic tonsillitis were selected. Patients were divided into four groups according to their 25OHD levels. Patients with 25OHD levels 0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
1
0
1
Order By: Relevance
“…Additionally, more than two-thirds (68%) of the recurrent tonsillitis group had vitamin D deficiency compared to nearly one-third (32%) of the control group. These findings suggest that recurrent tonsillitis bouts were inversely proportional to vitamin D levels, and these were also in line with the findings of Al-Rawashdeh et al [ 8 ] and Safak et al [ 21 ], which showed a significant relationship between low vitamin D levels and recurrent tonsillitis. In another study, low serum vitamin D levels were linked to an increased risk for URT infections, using polymerase chain reaction (PCR) assay.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, more than two-thirds (68%) of the recurrent tonsillitis group had vitamin D deficiency compared to nearly one-third (32%) of the control group. These findings suggest that recurrent tonsillitis bouts were inversely proportional to vitamin D levels, and these were also in line with the findings of Al-Rawashdeh et al [ 8 ] and Safak et al [ 21 ], which showed a significant relationship between low vitamin D levels and recurrent tonsillitis. In another study, low serum vitamin D levels were linked to an increased risk for URT infections, using polymerase chain reaction (PCR) assay.…”
Section: Discussionsupporting
confidence: 92%
“…This epithelium is avascular and only a very few nonepithelial cells are found in a normal healthy person. In chronic infection as chronic tonsillitis, the circulation of blood is poor because of degenerative changes causing parenchymal fibrosis 5 , 18 . The fibrosis of the tonsillar tissue due to repeated tonsilitis result in damage to the barrier function of the tonsils with a local dysfunction of the immunity, which subsequently caused a persistent infection, at the same time inflammatory process succeed to proliferate and activates the fibroblastic producing collagen cells in addition to the immune cells to replace the immunologic active tissue with fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Safak et al reported that VEGF was higher in children with serum Vitamin D <20 ng/mL. The expression of VEGF increases vascular permeability and angiogenesis as a sign of the adaptive inflammatory response [19]. Another study in Auckland reported that 16% of children undergoing tonsillectomy were Vitamin D deficient, and 80% had <75 nmol/L [20].…”
Section: Discussionmentioning
confidence: 99%